Cobertura de programas preventivos en Chile. - Báchler, R. Roberto; Soto, P. Alex; Pinilla, V. Mabel; Encina, S. Luis (Cuadernos Médico Sociales, 2012)
Introduction: In order to have an impact on the level of health, Preventive Medicine Programs should have high population coverage. Objective: To study the coverage of preventive programs which were conducted in the Chilean Public Health System in 2007. Material and Methods: The coverage of preventive programs in the databases of the Department of Health Statistic and Information of the Chilean Ministry of Health in the year 2007 were reviewed. Results: The overall coverage of preventive programs as measured by the index of Preventive Medicine was 0.202. The health program aimed at < 6 years (children) was the one that recorded a greatest coverage (0.84). An intermediate level of coverage was observed in the women's program (0.34) and in that of elderly (0.29). Programs conducted for school children, teenagers, and adults presented a low coverage (<0.1). Discussion: The high coverage observed in the child health preventive program, has been a factor that has led to the improvement of the health status of this population group. Particularly, it has contributed to reduce the infant mortality in Chile. The country must create strategies to increase the coverage of preventive programs aimed at schoolchildren, teenagers and adults. Only in this way we can go on improving the level of population health.